2018
DOI: 10.1021/acs.joc.8b00486
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Evaluation of 2-Arylazocarboxylates and 2-Arylazocarboxamides as Mitsunobu Reagents

Abstract: 2-Arylazocarboxylate and 2-arylazocarboxamide derivatives can serve as replacements of typical Mitsunobu reagents such as diethyl azodicarboxylate. A systematic investigation of the reactivity and physical properties of those azo compounds has revealed that they have an excellent ability as Mitsunobu reagents. These reagents show similar or superior reactivity as compared to the known azo reagents and are applicable to the broad scope of substrates. p K and steric effects of substrates have been investigated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Extending from the semicarbazones, numerous zinc(II) complexes have been reported to form with Schiff base ligands, exhibiting applications in catalysis and demonstrating antibacterial and anticancer properties (Kasuga et al, 2003;Pieczonka et al, 2014). AAFs, however, have been underexplored as ligands yet have been indicated as reagents for the Mitsunobu reaction (Hirose, et al, 2018). As ligands, AAFs differ from semicarbazones in the manner of the 1,3-heterodiene motif; where the semicarbazones form a five-membered coordination ring through a Schiff base of type R-C N-NH(R)-C O, the azoformamide uses the R-N N-C O to generate the fivemembered metal-chelate.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Extending from the semicarbazones, numerous zinc(II) complexes have been reported to form with Schiff base ligands, exhibiting applications in catalysis and demonstrating antibacterial and anticancer properties (Kasuga et al, 2003;Pieczonka et al, 2014). AAFs, however, have been underexplored as ligands yet have been indicated as reagents for the Mitsunobu reaction (Hirose, et al, 2018). As ligands, AAFs differ from semicarbazones in the manner of the 1,3-heterodiene motif; where the semicarbazones form a five-membered coordination ring through a Schiff base of type R-C N-NH(R)-C O, the azoformamide uses the R-N N-C O to generate the fivemembered metal-chelate.…”
Section: Chemical Contextmentioning
confidence: 99%
“…DSC) analysis of 41a,b indicated that thermal decomposition occurred at much higher temperatures than those at which decomposition of 34 occurred. 30 We succeeded in catalytic Mitsunobu reaction for azo reagents, but a stoichiometric amount of PPh 3 is still required in this method. A well-designed cyclic phosphine oxide can be reduced to the corresponding phosphine by silane reagents, and O'Brien's group reported that this system was applicable to catalytic Wittig and Mitsunobu reactions.…”
Section: Syn Lettmentioning
confidence: 99%
“…To the best of our knowledge, our procedure is the first organocatalytic Mitsunobu reaction protocol in which the Mitsunobu reagent is regenerated directly with oxygen without the need of any additional reagents. A few catalytic procedures with either dialkyl azodicarboxylate or phosphane regeneration have been previously reported , . However, they require at least an extra catalyst or even a sacrificial oxidizing (other than oxygen) or reducing agent (Scheme A, left).…”
Section: Figurementioning
confidence: 99%
“…In the presence of triphenylphosphane, 2c forms the N(5) adduct, which is able to activate alcohols towards the esterification reaction with various carboxylic acids. Our procedure is catalytic from the point of view of the flavin and it is distinguishable from other catalytic Mitsunobu protocols, due to the direct regeneration of the Mitsunobu reagent by oxygen without the need of an additional catalytic system or sacrificial oxidant. Despite some limitations in substrate scope, this example clearly shows that the toxic and explosive dialkyl azodicarboxylates usually used in the Mitsunobu reaction could be replaced by environmentally benign biomimetic flavins.…”
Section: Figurementioning
confidence: 99%